2018
DOI: 10.1007/s00464-018-6500-x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma medication usage is significantly reduced following bariatric surgery

Abstract: Introduction Asthma is an important healthcare problem affecting millions in the United States. Additionally, a large proportion of patients with asthma suffer from obesity. These patients exhibit poor asthma control and reduced therapy response, increasing utilization of healthcare resources. Pulmonary symptoms improve after bariatric surgery (BS), and we hypothesized that asthma medication usage would decrease following BS. Methods A retrospective data analysis was performed in adult patients from a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
(40 reference statements)
0
25
0
Order By: Relevance
“…There is a clear need for more studies that consider the effect of a restrictive diet before surgery if one was employed. Finally, despite growing evidence that bariatric surgery could be beneficial for patients with asthma (7,9,92,93), to the best of our knowledge, no study has explored whether the airway/lung microbiome changes after bariatric surgery.…”
Section: Obesity Biology and Integrated Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear need for more studies that consider the effect of a restrictive diet before surgery if one was employed. Finally, despite growing evidence that bariatric surgery could be beneficial for patients with asthma (7,9,92,93), to the best of our knowledge, no study has explored whether the airway/lung microbiome changes after bariatric surgery.…”
Section: Obesity Biology and Integrated Physiologymentioning
confidence: 99%
“…At present, some postsurgical changes in the gut microbiome are correlated with parameters of metabolic syndrome. Furthermore, reduced asthma medication usage (93) and gut microbiome alterations were reported as early as 30 days following surgery (74), which is likely too soon for weight loss to have a large impact. Therefore, a central question is whether this improvement in asthma control is because of metabolic changes and whether these changes are caused by microbiome alterations.…”
Section: Bariatric Surgery Microbiome Alterations and Asthma Concurmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma medication usage was also reduced following LSG [30]. A retrospective analysis of 751 asthmatic patients, including 80 LSG patients, found that the number of prescribed asthma medications among all procedures significantly decreased by 27% at 30 days post-surgery, 37% at 6 months, 44% at 1 year, and 46% at 3 years [30].…”
Section: Asthmamentioning
confidence: 99%
“…Similar trends are found among men. Weight loss surgery remains the most effective treatment for moderate to severe obesity and resolution of obesity-related comorbidities [2][3][4][5][6][7]. Most bariatric operations have very low rates of morbidity and mortality [8] and are among the more commonly performed operations in the USA [9].…”
Section: Introductionmentioning
confidence: 99%